Penggunaan Sprachblasen Pada Media Komik Dalam Keterampilan Berbicara Bahasa Jerman - Rahmawati Rahmawati; Nurming Saleh; Misnah Mannahali (Universitas Negeri Makassar, 2021)
Abstract. This research is class action research consist of two cycles and is performed virtually. The aim of this research is to get information about the planning, the process and the result of using Sprachblasen on comic media in German speaking skills of student from XI MAN 1 Makassar. The data are qualitative and quantitative. The qualitative data are collected through the observations and the quantitative data through the result of speaking tests in the first and second cycles and analyzed through the percentage technique. The result of this research shows that the students' speaking skills is 70 in the first cycle and in the second cycle is 78. It means the students in class XI MAN 1 Makassar by using Sprachblasen on the comic media has increased the German speaking skills (8%)